Arsitektur Dan Peran Masjid Ghede Kauman Yogyakarta Dalam Lintas Sejarah - Umi Masfiah (State Institute of Islamic Studies (IAIN) Salatiga, 2012)
The history of masjid Gedhe Kauman has a meaning of a place of worship since its inception to the present. In addition to its function as a place of worship, mosques as areas struggle against the invaders, the islamization, and the place of cultural development. While at present time, the dominant function of Masjid Gedhe as a place of scientific studies, the social activities, and means of cultural preservation sekaten. The research was conducted using qualitative methods with the historcal approach to trying and to see things from the point of the point of the span time or diachronic, to see the change, the continuity, the omission, the leaps, and the baundaries, the depiction of various forms of collevtive experience in the past. Any disclosure could be viewed as a staging of the actualization or the experience. In the procces of collecting datas, researcher using observation, review of documents, and interviews. The purpose and function of this researvch is to enrich the treasures of religious studies contribute to a theoretical, as well as provide the function as input for the goverment in formulating policies with regard to meeting the needs of the literature and increase the love and concern for the relics of history for the comunity.